2010
DOI: 10.1021/la102467u
|View full text |Cite
|
Sign up to set email alerts
|

Replicable Multilayered Nanofibrous Patterns on a Flexible Film

Abstract: This report describes a simple method for the direct patterning of nanofibers on a flexible, insulating film. The method allows the replication of nanofibrous patterns from a single patterned electrode and the fabrication of multilayered patterns from various electrode shapes. The architecture of the fibrous patterns can be controlled by tailoring the ambient humidity, thickness of the insulating film, polarity of the electrode, and size of the patterned electrode. Using this novel technique, it is possible to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 25 publications
1
33
0
Order By: Relevance
“…Selective micro deposition is difficult due to electric field distortion induced by the film insulator, and because of that a good adherence between the spin coater plaques and the films is necessary [9]. Figure 1 show that a good contact between film and collector was obtained.…”
Section: Production and Morphologic Structurementioning
confidence: 95%
“…Selective micro deposition is difficult due to electric field distortion induced by the film insulator, and because of that a good adherence between the spin coater plaques and the films is necessary [9]. Figure 1 show that a good contact between film and collector was obtained.…”
Section: Production and Morphologic Structurementioning
confidence: 95%
“…Two types of fibrous membranes with different fiber orientations were fabricated using these collectors: PU fibers on the planarshaped collector randomly formed a fibrous membrane with randomly oriented microfibers, while on the parallel plate collector, the PU fibers were aligned between the parallel plates forming a fibrous membrane with uniaxially aligned microfibers. [24][25][26][27] The prepared PU microfibrous membranes were coated with PANI hair-like nanostructures using the dilute polymerization technique, [22] which is depicted in Figure 1b. The membranes were immersed in an aqueous solution containing 1 m HClO 4 (Samchun Pure Chemical, Korea), 6.7 × 10 −3 m ammonium persulfate (APS, Sigma Aldrich, USA), and 10 × 10 −3 m aniline monomer (Sigma Aldrich, USA).…”
Section: Sensor Fabricationmentioning
confidence: 99%
“…Most approaches have either varied the applied electric field (14,15) or the geometry of the collector electrode. (16)(17)(18)(19)(20)(21)(22)(23)(24) Controlling the applied electric field appears to be a promising means of controlling the pattern of the electrospun membranes. The chaotic and rapid motion of the jet cannot be suppressed at high voltages.…”
Section: Introductionmentioning
confidence: 99%
“…Cho et al demonstrated that electrospun nanofibers can be deposited selectively with microscale resolution, and can be aligned onto flexible insulators, by controlling the geometry of the electrode. (23) These reports suggest considerable scope for improving the breathability of waterproof fabrics by controlling the structure of electrospun membranes.…”
Section: Introductionmentioning
confidence: 99%